Reasons for the low productivity of the Bashkirian stage oil deposits on the southwestern slope of the South Tatar arch - Korolev Eduard; Eskin Aleksey; Korolev Albert; Barieva Enza; Zamaletdinov Roman (E3S Web of Conferences, 2024)
Oil deposits of the Bashkirian stage of low-amplitude uplifts on the southwestern slope of the South Tatar arch are considered. It has been established that in the sections of the Bashkirian stage, only the upper two oil deposits are potentially productive. The reservoir rocks are composed of leached packstone-grainstone. The oil productivity of the upper oil reservoir is determined by the intensity of leaching of carbonate rocks and the nature of oil saturation, while the lower one is determined by the degree of oxidation of oils and the manifestation of secondary mineralization. Oxidation of oil from the lower reservoir oil deposit is associated with the penetration of peripheral stratal water enriched with sulphate ions and magnesium ions. Deposition of diagenetic calcite, dolomite and gypsum-anhydrite aggregates in previously formed leaching caverns leads to a decrease in porosity and connectivity within reservoir layers. For low-amplitude uplifts, there is a tendency for oil productivity to decrease as the proportion of diagenetic mineralization increases.